2022
DOI: 10.1186/s13041-022-00926-7
|View full text |Cite
|
Sign up to set email alerts
|

New neurons in old brains: implications of age in the analysis of neurogenesis in post-mortem tissue

Abstract: Adult neurogenesis, the proliferation and integration of newly generated neurons, has been observed in the adult mammalian hippocampus of many species. Numerous studies have also found adult neurogenesis in the human hippocampus, but several recent high-profile studies have suggested that this process is considerably reduced in humans, occurring in children but not in adults. In comparison, rodent studies also show age-related decline but a greater degree of proliferation of new neurons in adult animals. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…For instance, although NR2A and NR2B subunits appear to be rapidly degraded after death (Wang et al, 2000), most subunits of N‐methyl‐ d ‐aspartate (NMDA) and α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid (AMPA)‐type glutamate receptors are stable at ~18 h PMD. Studies performed by Boekhoorn et al (2006) and Terstege et al (2022) suggested enhanced susceptibility of DCX to postmortem degradation. These authors observed that, in rat samples with artificially induced prolonged PMDs (≥8 h), DCX staining disappears from the dendrites and is restricted to the soma and nucleus of immature DGCs.…”
Section: Critical Steps To Study Human Ahn By Ihcmentioning
confidence: 94%
See 2 more Smart Citations
“…For instance, although NR2A and NR2B subunits appear to be rapidly degraded after death (Wang et al, 2000), most subunits of N‐methyl‐ d ‐aspartate (NMDA) and α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid (AMPA)‐type glutamate receptors are stable at ~18 h PMD. Studies performed by Boekhoorn et al (2006) and Terstege et al (2022) suggested enhanced susceptibility of DCX to postmortem degradation. These authors observed that, in rat samples with artificially induced prolonged PMDs (≥8 h), DCX staining disappears from the dendrites and is restricted to the soma and nucleus of immature DGCs.…”
Section: Critical Steps To Study Human Ahn By Ihcmentioning
confidence: 94%
“…However, subsequent research revealed that, although certain proteins may show particularly rapid postmortem degradation (Boekhoorn et al, 2006;Sorensen, 1984;Terstege et al, 2022), especially in certain regions of the brain (Siew et al, 2004), the immunodetection of most proteins and enzymes is moderately resistant to this phenomenon (Blair et al, 2016;Ritchie et al, 1986;Schut et al, 2017;Wang et al, 2000). For instance, although NR2A and NR2B subunits appear to be rapidly degraded after death (Wang et al, 2000), most subunits of N-methyl-Daspartate (NMDA) and α-amino-3-hydroxy-5-methyl- reported that this phenomenon is accentuated in aged animals (Terstege et al, 2022). DCX is detected in the human DG at prolonged PMD intervals (Flor-Garcia et al, 2020;Moreno-Jimenez et al, 2019Terreros-Roncal et al, 2021).…”
Section: Postmortem Delaymentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, from their published images, similar DCX + cell shapes were observed. PMI is another key element for Human IHC work (Terstege et al, 2022). Fresh tissue is reported to allow for the detection of DCX via IHC (Terstege et al, 2022).…”
Section: Human Ahnmentioning
confidence: 99%
“…PMI is another key element for Human IHC work (Terstege et al, 2022). Fresh tissue is reported to allow for the detection of DCX via IHC (Terstege et al, 2022). Moreno-Jimenez et al selected tissues which only have 2.5 hours to 10 hours of PMI (Moreno-Jimé nez et al, 2019).…”
Section: Human Ahnmentioning
confidence: 99%